A study of the effect of neoadjuvant chemotherapy with FAC regime in locally advanced breast carcinoma - Gopal, Ajesh; Anjit, U. (International Journal of Research in Medical Sciences, 2017)
Background: Cases of carcinoma breast with TNM stage 3 are considered as locally advanced breast cancer. This study was done to demonstrate the effect of neoadjuvant chemotherapy in cases of stage 3 technically inoperable breast cancers. As neoadjuvant chemotherapy is an already established form of treatment, its effect on ‘complete clinical response and pathological response’ were studied. Methods: This prospective study was carried out in department of general surgery of Medical college, Thiruvananthapuram after obtaining approval from research ethical committee. Relevant data of chemotherapy was collected from department of Radiotherapy and Histopathological data was collected from department of Pathology. 25 cases of locally advanced breast carcinoma were studied. These patients were started on treatment with FAC regime and the response was assessed. Results: In this study 20% of patients had complete clinical response at the completion of 3 cycles of chemotherapy with FAC regime. 48% had partial response. In 32% of patients, stasis was observed. None showed increase in tumor size during treatment. Conclusion: The study demonstrated the effectiveness of neoadjuvant chemotherapy in downstaging the tumor enabling definitive surgery with less morbidity. It also showed a complete clinical and pathological response in a significant number of patients.